2017
DOI: 10.20960/nh.973
|View full text |Cite
|
Sign up to set email alerts
|

The association between high blood pressure, physical fitness and fatness in adolescents

Abstract: The association between high blood pressure, physical fi tness and fatness in adolescents Resumen Introducción: la hipertensión es un problema de la salud y es de importancia nacional. Es un factor de riesgo importante para la aparición de la aterosclerosis y enfermedades cardiovasculares, cerebrovasculares y enfermedades renales que están liderando o están entre las principales causas de mortalidad y la morbilidad como en la nuestra, también en los países más desarrollados y menos desarrollados. Objetivo: el … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
8
0
7
Order By: Relevance
“…Moreover, abdominal adiposity in combination with a poor PF are directly associated with serious diseases [77,78]. The association between body composition parameters (waist circumference, percentage of body fat, and BMI) and performance in numerous fitness tests has been extensively studied in Europe [79] and non-European countries [80,81], thus determining the need for preventive work and the monitoring of the health status of adolescents. If we examine the results of the tests of the AFB, a better performance can be observed among those participants with N-O waist , N-O fat , and N-O weight in the long jump, speed/agility, and cardiorespiratory resistance tests.…”
Section: Fitness Performance In Boys and Girls With And Without O Waimentioning
confidence: 99%
“…Moreover, abdominal adiposity in combination with a poor PF are directly associated with serious diseases [77,78]. The association between body composition parameters (waist circumference, percentage of body fat, and BMI) and performance in numerous fitness tests has been extensively studied in Europe [79] and non-European countries [80,81], thus determining the need for preventive work and the monitoring of the health status of adolescents. If we examine the results of the tests of the AFB, a better performance can be observed among those participants with N-O waist , N-O fat , and N-O weight in the long jump, speed/agility, and cardiorespiratory resistance tests.…”
Section: Fitness Performance In Boys and Girls With And Without O Waimentioning
confidence: 99%
“…Medications regularly require long administration periods as many individuals regain their lost weight when medication is suspended. The suspension of medication use by individuals is typically due to their major side effects, cost, and a potential lack of insurance coverage [ 52 ].…”
Section: Treatment Of Obesitymentioning
confidence: 99%
“…Most of the findings related to RHR come from investigations aimed to establish a relationship between RHR and risk factors for cardiovascular diseases, such as blood pressure and inflammatory markers. The literature has reported that adolescents and young adults with better performance in physical fitness tests have lower odds of high blood pressure, hypercholesterolemia, and cardiovascular dysfunction, as well as lower RHR 23,24 . The healthrelated issues have positive changes in RHR.…”
Section: Introductionmentioning
confidence: 99%